2019
DOI: 10.5935/0103-507x.20190038
|View full text |Cite
|
Sign up to set email alerts
|

Early mobilization protocols for critically ill pediatric patients: systematic review

Abstract: Objective To describe the existing early mobilization protocols in pediatric intensive care units. Methods A systematic literature review was performed using the databases MEDLINE ® , Embase, SciELO, LILACS and PeDRO, without restrictions of date and language. Observational and randomized and nonrandomized clinical trials that described an early mobilization program in patients aged between 29 days and 18 years admitted to the pediatric intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
17
0
7
Order By: Relevance
“…Interventions performed during hospitalization ( 12 - 14 ) can cause deficits in the overall functional status of children. ( 3 , 14 - 16 ) Studies have shown that functional decline is directly influenced by clinical variables ( 3 , 17 ) and by risks inherent to the medical intervention and the underlying disease. ( 15 )…”
Section: Introductionmentioning
confidence: 99%
“…Interventions performed during hospitalization ( 12 - 14 ) can cause deficits in the overall functional status of children. ( 3 , 14 - 16 ) Studies have shown that functional decline is directly influenced by clinical variables ( 3 , 17 ) and by risks inherent to the medical intervention and the underlying disease. ( 15 )…”
Section: Introductionmentioning
confidence: 99%
“…Esses achados podem ser reflexo da ausência ou desconhecimento de protocolo de mobilização precoce na unidade de trabalho relatada por 77,4% dos participantes, o que corrobora com a literatura, que afirma que a ausência de protocolos e diretrizes escritas e o conhecimento da equipe multiprofissional são possíveis barreiras para a implementação da mobilização precoce. 5,10 A literatura mostra que a implementação de programa de estudo, engajamento, execução e avaliação para a mobilização precoce dentro de uma unidade de terapia intensiva pediátrica (UTIP) envolvendo treinamento de toda a equipe obteve como resultado um maior engajamento dos profissionais na mobilização precoce, além de aumentar a quantidade de mobilização após o programa. 8 De acordo com Choong et al 1 , que escreveram um guia prático de recomendações para mobilização precoce baseado na literatura e com a experiência de uma equipe multiprofissional de 10 experts na sua área de atuação, a mobilização precoce em pediatria deve fazer parte do esquema de cuidado "ABCDEFGH", onde A seria atenção a analgesia, evitar níveis altos de sedação, permitir o despertar; B seria permitir a respiração espontânea; C seria o manejo da sedação e analgesia; D indica a prevenção de delírio, vigilância e manejo; E indica mobilização precoce e exercício; F indica envolvimento familiar e empoderamento da família; G refere-se a uma boa nutrição; H refere-se ao humanismo.…”
Section: Atuação Da Equipe Multiprofissional Na Mobilização Precoce De Neonatos No Pósoperatóriounclassified
“…Although definitions vary, for the purposes of this review, mobility interventions can be considered to include all physical activities aimed at preventing muscle wasting and preserving or enhancing functional mobility and cognitive recovery. Early mobilization refers to such activities implemented in the first few days after admission to PICU (after initial medical stabilization), although exact definitions and timepoints vary (12,49,50). Early mobility and PICUbased rehabilitation prescription is not determined or supported by "rocket science" (there are not yet any rigorous clinical trials yielding high-level evidence), and therefore cannot be prescriptively and prohibitively defined.…”
mentioning
confidence: 99%
“…Without evidence to the contrary, good PICU mobilization practice can be summarized as following individualized, goaldirected planning to facilitate critically ill children to move as soon after PICU admission as appropriate, at a level and pace suitable to their age, condition and developmental level. Even where protocols have been implemented for research purposes, the majority have planned EM activities individually (49). Having unit-based mobility protocols are recommended, as these have been associated with improved mobility practice, and may reduce the potential for implicit bias in clinical decision making (32,49).…”
mentioning
confidence: 99%
See 1 more Smart Citation